That time I got reincarnated as a slime. 12 - Fuse (Manga author); Kawakami, Taiki; Fuse (Manga author) (Kodansha Comics, 2020)
"With the help of Queen Ramiris, the children are now in stable condition and should lead normal lives, much to Rimuru's relief. But all is not well... In fact, there are forces of humankind in this fantasy world that do not look kindly upon a slime-led nation of monsters. And now, insidious threats to Rimuru and the country of Tempest may be lurking around every corner!"--Provided by publisher.